Mizan and the green consumer: Exploring eco-friendly packaged food adoption among middle-class Muslim consumers - Anggryani, Lisa; Razak, Syaparuddin; Hamzah, Aksi; Sahaka, Arifin; Sabbar Dahham Sabbar (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2025)
This study examines the adoption of eco-friendly packaged foods among middle-class Muslim communities, emphasizing their role in promoting sustainable lifestyles. It fills a research gap by integrating Islamic ethical principles, specifically the concept of balance (Mizan), into sustainable product adoption models. Data collection was performed through cluster sampling of 240 respondents. The study employed Partial Least Squares Structural Equation Modeling (PLS-SEM) to handle complex models with small to medium sample sizes and its exploratory and confirmatory analysis capacity. The findings show that all proposed relationships are statistically significant. As an Islamic ethical principle of balance, Mizan plays a key role in shaping responsible waste management practices. Along with product design and business models, Mizan encourages more mindful and sustainable waste handling. Effective waste management then enhances environmental awareness, directly promoting sustainable product adoption. Product design also directly affects adoption behavior, while natural resource management and technological innovation contribute to the development of sustainable business models. These findings highlight Mizan as a foundational ethical value that guides individual environmental behavior and strengthens the structural pathways leading to sustainable product adoption.